Pengaruh Kunjungan Wisatawan Gunung Bulusaraung Terhadap Pendapatan Usaha Mikro Kecil Dan Menengah (UMKM) Di Desa Tompo Bulu - Asrawati, Dini; Dunakhir, Samirah; Afiah, Nur (CV. ULIL ALBAB CORP, 2024)
This study aims to determine whether there is an influence of tourist visits to the Mount Bulusaraung tourist attraction on the income of MSMEs in Tompo Bulu Village. The variables in this study are Tourist Visits as the independent variable and MSME income as the dependent variable. The population of this study is MSME operators at the Mount Bulusaraung tourist site, with a sample size of 5 MSME operators around the tourist attraction. Data collection techniques used include observation, interviews, and documentation. The data analysis method used is Qualitative Descriptive Analysis. The results of this study indicate that tourist visits to Mount Bulusaraung have an impact on the income of MSMEs around the area. Visiting tourists directly contribute to the local economy through the purchase of products and the use of local MSME services. Tourist visits have a positive effect by increasing the demand for products and services offered by local MSMEs. Based on the research conducted, MSME income increased by approximately 10% when there were tourist visits. This indicates that the more visitors that come, the greater the percentage increase in MSME income.